(untitled) (Asian Journal of Agriculture, 2024)
Abstract. Yaried AA, Bullo MS. 2025. Determinants of women’s participation in income generating activities in western Ethiopia. Asian J Agric 9: 84-93. Participating in various income generating activities can improve women’s living standards by providing additional income, increasing agricultural productivity, reducing poverty and improving food security. This study focuses on assessing determinants of women’s participation in income generating activities in Itang special district of Gambella region. Primarily, Itang Special District was selected purposively among thirteen districts and 168 respondents were selected by using simple random sampling method. The data for this study was collected from both primary and secondary data sources. The descriptive analysis revealed that 62 (36.9%) of the households were farm participants, 86 (51.2%) were non-farm, and 20 (11.9%) were off-farm participants, respectively. Correspondingly, the multinomial logit model indicated that education status, household size, land size, livestock holding, access to credit, access to extension contacts, distance to main road, access to training, access to infrastructures, and access to market information is enormously significant variables that affect women’s participation in income generating activities. In conclusion, women’s participation in income generating activities has a greater role on improvements of their means of living. Therefore, government agencies, policymakers, and NGOs should pay attention to strengthening rural women households’ participation in various income generating activities to improve their means of living.